1,2,4-triazole-3-carboxamides induces G2/M cell cycle arrest in ovarian cancer cell lines - E. M. Zhidkova; L. E. Grebenkina; V. P. Maksimova; D. D. Grigoreva; E. A. Mikhina; A. V. Matveev; M. G. Yakubovskaya; E. A. Lesovaya (Сибирский онкологический журнал)
Introduction. Ovarian cancer is one of the most common gynecological cancers worldwide, which is difficult to diagnose and treat. the high mortality rate from ovarian cancer makes the development of new therapeutic drugs relevant. Ribavirin (RBV), commonly used antiviral agent, revealed the anticancer potential, however, it led to the development of severe side effects as well. RBV derivatives were previously synthesized and tested as putative anticancer drugs in the models of hematological malignancies. The aim of this study was to estimate the anticancer effects of and RBV derivatives (MGs) in ovarian cancer cells in vitro. Material and Methods. Cytotoxic and cytostatic effects of the MGs on ovarian cancer cells (OVCAR3 and OVCAR4) were assessed using the MTT assay and cell counting with trypan blue staining. distribution of cell cycle phases and induction of apoptosis was evaluated using flow cytometry with propidium iodide and annexin V-FITC staining. Results. 1,2,4-triazole-3-carboxamides inhibited the proliferation and induced cell cycle arrest of ovarian cancer cells in vitro. Conclusion. these results provide the rationale for further studies of 1,2,4-triazole-3-carboxamides as anticancer drugs.